TO THE QUESTION OF THE EXISTENCE OF CENTAURS - EVENTS IN COSMIC RAYS - Pokrovskiy, N.S. (Academic Scientific Journal of Computer Science, 2020)
One of the first exotic phenomena observed in the 80s of the last century was an event registered by a calorimetric type installation. In this event, an anomalous relationship was observed between charged and neutral hadrons, arising from the collision of a high-energy particle with a carbon nucleus. In accordance with the principle of isotopic invariance, the number of neutral pions should be equal to the number of charged pions. The event, which was recorded by Japanese physicists, contained only charged peonies with no neutral [1]. This event was named "Centaur". Until now, such events have not been observed in accelerator experiments. The article presents the results of searching for such events in experiments at the DESY HERA collider. For the candidates for Centaur events and for all other events, constructed distributions by the type of fitability of charged tracks in CTD. Since the absence of neutral particles in events is explained by methodological reasons, "Centaur" events were not detected in electron-proton interactions at the ZEUS facility.